Obstructive sleep apnoea: From pathogenesis to treatment: Current controversies and future directions - Eastwood, Peter; Malhotra, A.; Palmer, L.; Kezirian, E.; Horner, R.; Ip, M.; Thurnheer, R.; Antic, N.; Hillman, D. (Wiley-Blackwell Publishing Asia, 2010)
Obstructive sleep apnoea (OSA) is a common disease, recognized as an independent risk factor for a range of clinical conditions, such as hypertension, stroke, depression and diabetes. Despite extensive research over the past two decades, the mechanistic links between OSA and other associated clinical conditions, including metabolic disorders and cardiovascular disease, remain unclear. Indeed, the pathogenesis of OSA itself remains incompletely understood. This review provides opinions from a number of leading experts on issues related to OSA and its pathogenesis, interaction with anaesthesia, metabolic consequences and comorbidities, cardiovascular disease, genetics, measurement and diagnosis, surgical treatment and pharmacotherapeutic targets. © 2010 Asian Pacific Society of Respirology.